Acute Changes on Pulmonary Pressure Following Percutaneous Closure of Secundum Atrial Septal Defect - Jessica Wiryanto; Ingrid M. Pardede; Sunanto Ng (ACI (Acta Cardiologia Indonesiana), 2017)
Pulmonary hypertension is a common complication of congenital heart disease due to systemic – pulmonary circulation shunt which if left uncorrected leads to increased pulmonary artery pressure, vascular remodeling and further increase of pulmonary vascular resistance. Percutaneous closure of the defect interrupts this shunt thus reducing right heart and pulmonary circulation load and pulmonary artery pressure. In this paper we present two cases of percutaneous secundum atrial septal defect closure complicated by pulmonary hypertension along with echocardiographic evaluation of cardiopulmonary hemodynamic changes before and shortly after device closure. Forty years old and thirty three years old females presented to our clinics with classical symptoms of atrial septal defects, assessment revealed TVG of 37 mmHg and 30 mmHg,shortly after the procedure patient was re-evaluated and revealed TVG of 39 mmHg and 23 mmHg respectively. From these cases we conclude that changes in pulmonary artery pressure is not constantly found after device closure. However both patients display improvements in functional capabilities.